Tradisi Massuru' dan Pertobatan Dalam Injil Sinoptik - Rumbi, Frans Paillin (Institut Agama Kristen Negeri Toraja, 2018)
This paper juxtaposes two models of wrong forgiveness and sin. Massuru 'in Toraja culture and repentance in the gospel. This research study is explanatory in order to explain the concept of masu suru and repentance from the theological roots that shape it. The materials used are sourced from the literature but in dialogue with the observations or experiences that the author has encountered in the field, both when observing the way the Toraja interpret their traditions and interpret liturgical confessions in the congregation. The results of this study found that massuru and repentance had a more or less the same basic pattern, which was initiated by false recognition or sin, forgiveness and finally peace. Another similarity is improving behavior, reestablishing relations with God and fellow creatures. But there are differences in terms of initiative, targets in the visible and inner aspects, atonement victims. Massuru 'can be used as a model for confession in congregations and repentant pastoral models, but it needs to adjust its meaning to the values of the contain of Christian teachings. AbstrakTulisan ini menyandingkan dua model pengampunan salah dan dosa. Massuru’ dalam kebudayan Toraja dan pertobatan dalam Injil. Kajian penelitian ini bersifat eksplanasi untuk menjelaskan konsep massuru’ dan pertobatan dari akar tradisi-teologis yang membentuknya. Bahan-bahan yang digunakan bersumber dari kepustakaan tetapi di dialogkan dengan pengamatan atau pengalaman yang selama ini penulis jumpai di lapangan, baik ketika mengamati cara orang Toraja memaknai tradisinya maupun memaknai liturgi pengakuan dosa dalam jemaat. Hasil penelitian ini menemukan bahwa massuru' dan pertobatan memiliki pola dasar yang kurang lebih sama, yakni dimulai dengan pengakuan salah atau dosa, pengampunan dan akhirnya perdamaian. Kesamaan lain yakni memperbaiki perilaku, membangun kembali relasi dengan Allah dan sesama ciptaan. Tetapi terdapat perbedaan dari segi inisiatif, sasaran pada aspek kelihatan dan batin, korban pendamaian. Massuru' dapat digunakan sebagai model akta pengakuan dosa dalam jemaat maupun model pastoral tobat, akan tetapi perlu menyesuaikan maknanya dengan nilai-nilai yang terkandung alam ajaran Kristen.